Pengalaman Perawat dalam Melaksanakan Spiritual Care di Ruang Rawat Isolasi COVID-19 - Abul A’la Tarigan; Siti Zahara Nasution; Hasnida Hasnida (Journal of Telenursing (JOTING), 2023)
This study explores the experiences of nurses who have carried out spiritual care in the COVID-19 isolation room at the University of North Sumatra Hospital. The method used is qualitative research with purposive sampling data collection techniques. The results of the study show that four themes can be used as experiences for nurses in carrying out spiritual care in the COVID-19 isolation room at USU Hospital, namely: 1) Carrying out nursing care according to standard operating procedures for handling COVID-19 patients; 2) Apply the ethical principles of the nursing profession in treating COVID-19 patients; 3) Carry out efforts through collaboration with families in fulfilling the spiritual needs of COVID-19 patients; and 4) Obstacles that hinder the implementation of nursing care for COVID-19 patients. In conclusion, in carrying out nursing care for COVID-19 patients, nurses use the careful nursing theory model. Keywords: Spiritual Care, COVID-19